Rancang Bangun Perajang Ubi Kayu Pisau Horizontal - Lutfi, Musthofa; Setiawan, Sigit; Nugroho, Wahyunanto A. (Jurnal Rekayasa Mesin, 2010)
Cassava is an important source of food calories as well as source of other products in Indonesia. Utilization and processing potential of cassava are widely diverse. One of processed commodity of cassava is crispy chips. In crispy chips production, there need an efficiently and a good copper. The aim of this research is to design a cassava chopper powered by electrical motor and equipped with horizontal blade. Furthermore, this study aimed to identify the performance of designed chopper. The result of the design step is a chopper that has well functionally. The designed chopper has four parts; frame, transmission, hopper and cutter blade. It is powered by 0,25 kW electric motor and equipped with rotation speed control. In the design of the chopper with a horizontal blade, the cutting blades are not spinning stationary but changed into backward and forward movement. The highest specific energy as a result of performance identification is 42.50 Joules / kg. The highest working capacity is 62.550 kg / h occurs in motor rotation of 170 rpm. Keywords : Design, Chopper, horizontal blade, cassava, crispy chips.